Aset Digital Bitcoin sebagai Objek Harta Waris dalam Perspektif Hukum Islam Kontemporer - Febrianti Dyahsitasari; Muhammad Yassir (BUSTANUL FUQAHA: Jurnal Bidang Hukum Islam, 2023)
This research aims to examine the views of contemporary Islamic law regarding bitcoin digital assets as objects of inheritance. In this research, a normative juridical method is used which involves library legal research by examining library materials or secondary data with data collection techniques using a conceptual approach. The results show that bitcoin meets the criteria to be used as inherited property because the nature of bitcoin assets is in accordance with the nature of property, but contemporary Islamic scholars differ in opinion regarding the law of using bitcoin, the Indonesian Ulema Council itself forbids bitcoin as a currency and commodity without underlying, and legalizes bitcoin as a commodity with underlying, so that the law of inheritance also depends on the opinion or fatwa that is trusted, because fatwa is not binding.